INVERSION OF EARTHQUAKE FOCAL MECHANISMS TO OBTAIN THE SEISMOTECTONIC STRESS IV-A NEW METHOD FREE OF CHOICE AMONG NODAL PLANES - Angelier Ja. (My University, 2002)
A new method is presented, to obtain the stress state that best accounts for a set of double couple focal mechanisms of earthquakes. This method is based on the slip shear stress component (SSSC) criterion. The sum of the SSSC values is maximized as a function of four unknowns that describe the reduced stress tensor, including the orientations of the principal stress axes and the ratio between the principal stress differences. This new method combines two advantages. First, no choice between the nodal planes of each focal mechanism is needed, because of the intrinsic properties of the SSSC. Secondly, the runtime is negligible regardless of the size of the data set, because the inverse problem is solved by analytical means so that the numerical aspects are reduced to a minimum. For these reasons, the SSSC-based inversion is easily included in a variety of processes for separating or refining the data. A typical set of focal mechanisms of earthquakes in Taiwan is processed to illustrate the application and potential of the new method.
Keywords: EARTHQUAKE; FOCAL MECHANISM; INVERSION; SEISMOTECTONICS; STRESS; TENSOR